Exploring Discourses of Appropriation: Collecting Modern Canadian Cultural Identity - Little, Sarah E. (My University, 2012)
By applying Canadian literary theory, museum theory, and material culture theory to 20th and 21st century Canadian literature, I argue that physical objects reflect Canada's continued engagement in colonial practices and the nation's resistance to acknowledging these practices. The act of selecting and including (which is also necessarily an act of excluding) objects in personal and institutional collections speak to the anxiety of the Euro-Canadian settler that is produced by a conflicting sense of privilege and colonial complicity. Collecting is a means of negotiating self- and shared knowledge, and by re-collecting and repatriating those things that haunt us we come closer to recognizing ourselves. Re-reading ourselves through objects will allow us to confront this anxiety and its implications, to destabilize the Euro-Canadian settler-as-victim, and to move forward as a nation.
Keywords: material culture; collecting; Canadian identity; Canadian literature; literary theory; display politics; museums; colonial politics; Literature in English, North America; Literature in English, North America